STUDI PENGEMBANGAN LAHAN RAWA LEBAK POLDER ALABIO HULU SUNGAI UTARA KALIMANTAN SELATAN - Nadya Ul-Haq Mahmud (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2021)
The potential and area of swamps in Indonesia are very large, but the development of swamps is still small. The key success factor in swamps development lies in the water management system. The Alabio polder is the result of the development of a nontidal swamp with a polder system with an area of ± 6000 Ha located in the Alabio area, Danau Panggang District, South Kalimantan. Until now, Polder Alabio has not been working optimally, so rice production in this land has not been as expected. This paper aims to identify problems in the development of the Alabio Polder nontidal swamp. The method used in this study is to use literature studies taken from various scientific sources, either in the form of scientific articles, activity reports/studies related to the Alabio Polder. The study results showed that the water management at the Alabio Polder is still not functioning optimally. The main problems in the development of the Alabio Polder are the irrigation, drainage, and water structures that are not functioning properly, as well as the maintenance that has not been carried out routinely and properly. Irrigation channels, drainage, and water structures that do not function properly cause the quantity of water (discharge) to not be flowed properly to the entire land so that it also impacts the water quality in the land which is not good. Some solutions that can be done to overcome the problems at the Alabio Polder are to carry out regular and periodic repairs and maintenance of irrigation and drainage channels as well as maintenance of water buildings in the Alabio Polder.